Trichostatin C Synergistically Interacts with DNMT Inhibitor to Induce Antineoplastic Effect via Inhibition of Axl in Bladder and Lung Cancer Cells - Chenyin Wang; Lijuan Lei; Yang Xu; Yan Li; Jing Zhang; Yanni Xu; Shuyi Si (MDPI AG, 2024)
Aberrant epigenetic modifications are fundamental contributors to the pathogenesis of various cancers. Consequently, targeting these aberrations with small molecules, such as histone deacetylase (HDAC) inhibitors and DNA methyltransferase (DNMT) inhibitors, presents a viable strategy for cancer therapy. The objective of this study is to assess the anti-cancer efficacy of trichostatin C (TSC), an analogue of trichostatin A sourced from the fermentation of Streptomyces sp. CPCC 203909. Our investigations reveal that TSC demonstrates potent activity against both human lung cancer and urothelial bladder cancer cell lines, with IC50 values in the low micromolar range. Moreover, TSC induces apoptosis mediated by caspase 3/7 and arrests the cell cycle at the G2/M phase. When combined with the DNMT inhibitor decitabine, TSC exhibits a synergistic anti-cancer effect. Additionally, protein analysis elucidates a significant reduction in the expression of the tyrosine kinase receptor Axl. Notably, elevated concentrations of TSC correlate with the up-regulation of the transcription factor forkhead box class O1 (FoxO1) and increased levels of the proapoptotic proteins Bim and p21. In conclusion, our findings suggest TSC as a promising anti-cancer agent with HDAC inhibitory activity. Furthermore, our results highlight the potential utility of TSC in combination with DNMT inhibitors for cancer treatment.